2018
DOI: 10.3906/sag-1802-11
|View full text |Cite
|
Sign up to set email alerts
|

Identification of Candida species by restriction enzyme analysis

Abstract: The frequency of invasive fungal infections has increased substantially during the past two decades and it has become a major cause of morbidity and mortality in immunocompromised patients. Aspergillosis, candidiasis, cryptococcosis, and zygomycosis are the main invasive fungal infections observed in these patients (1). Among the fungal pathogens, Candida species are the most common cause of invasive fungal infections (2,3). Candida species rank as the fourth most common cause of nosocomial bloodstream infecti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
2
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…strains (MwoI for the totally of the species, and BslI for C. parapsilosis and C. tropicalis strains). The restriction digestion with MwoI was able to distinguish between five different species ( C. albicans , C. krusei , C. guilliermondii , C. kefyr , and C. glabrata ), while BslI digestion could distinguish between C. tropicalis and C. parapsilosis [238]. Another study summarized that phenotypic and molecular methods (PCR-RFLP) resulted in the identification of 65.2% and 96.6% of 204 Candida spp.…”
Section: Molecular Methods Used To Detect Yeastsmentioning
confidence: 99%
“…strains (MwoI for the totally of the species, and BslI for C. parapsilosis and C. tropicalis strains). The restriction digestion with MwoI was able to distinguish between five different species ( C. albicans , C. krusei , C. guilliermondii , C. kefyr , and C. glabrata ), while BslI digestion could distinguish between C. tropicalis and C. parapsilosis [238]. Another study summarized that phenotypic and molecular methods (PCR-RFLP) resulted in the identification of 65.2% and 96.6% of 204 Candida spp.…”
Section: Molecular Methods Used To Detect Yeastsmentioning
confidence: 99%
“…The ITS region of ribosomal DNA (rDNA) is the most useful genetic marker for rapid and accurate molecular identification of Candida species and phylogenetic studies due to its region sequence variability among different species [15,[45][46][47]. The ITS 1 and ITS 2 are two vital non-coding regions composed of conservative and variable subregions outside and inside respectively [45].…”
Section: The Internal Transcribed Spacer Marker For Candida Species I...mentioning
confidence: 99%
“…Biochemical profiling based on vibrational spectroscopy reflects the variability of chromosomal patterns and DNA content of clinical isolates of Candida species and can facilitate diagnosis and targeted therapy of candidiasis [18] . Restriction enzyme analysis with Mwol and BslI can be used for Candida species identification in situations where rapid identification is necessary or conventional methods are problematic [19] . The application of C. albicans microarrays in early studies on pathogenesis, cell biology, antifungal susceptibility and diagnostics confirmed their usefulness, and the results showed good correlations with data obtained with other techniques.…”
Section: Diagnosismentioning
confidence: 99%